Dahuang Fuzi Baijiang decoction restricts progenitor to terminally exhausted T cell differentiation in colorectal cancer. Issue 5 (3rd April 2022) - Xu, Yihua; Wang, Hao; Wang, Tao; Chen, Chunhui; Sun, Ruibo; Yao, Wanyu; Ma, Ye; Zhang, Qingyuan; Wu, Liyi; Zeng, Shanmei; Sun, Xuegang
Abstract: Obesity increases the risk of colorectal cancer (CRC) by 30%. The obese tumor microenvironment compromises antitumor immunity by eliciting exhausted T cells (Tex). Hypothesizing that Dahuang Fuzi Baijiang decoction (DFB) is a combined classical prescription from the "Synopsis of Prescriptions of the Golden Chamber". We first determined that DFB regresses tumor growth in high‐fat diet–induced obese mice by expanding the TIM3 − subset with intermediate expression of programmed cell death‐1 (PD‐1 int TIM 3− ) and restricting the PD‐1 hi TIM3 + subset. Transcription factor 1 (TCF1) is highly expressed in the PD‐1 int TIM3 − subset but is absent in PD‐1 hi TIM3 + cells. We next confirmed that progenitor PD‐1 int TCF + cells robustly produce tumor necrosis factor‐α (TNFα) and interferon‐γ, whereas terminally differentiated PD‐1 int TCF + cells have defects in generating TNFα. With transgenic ob / ob mice, we found that DFB produces cooperative efficacy with anti‐PD‐1 (αPD‐1) by limiting the PD‐1 hi Tim3 + subset and amplifying the PD‐1 int TCF + population. Finally, we defined the recombinant chemokine C‐C‐motif receptor 2 (CCR2) + CD8 + subset as terminal Tex and identified that the differentiation from progenitor to terminal Tex is driven, at least in part, by the chemokine (C‐C motif) ligand 2 (CCL2)/CCR2 axis. The CCR2 inhibitor enhances the response to αPD‐1 by promoting the counts of progenitor Tex. Altogether, DFB dampens CCL2 and preserves progenitor Tex in the obese microenvironment to restrain CRC progression. These findings provide unambiguous evidence that the traditional Chinese formula DFB can prevent tumor progression by modulating adaptive immunity and establish a strong rationale for further clinical verification. Abstract : Dahuang Fuzi Baijiang decoction (DFB) produces cooperative efficacy with anti‐programmed cell death‐1 (PD‐1) by limiting the PD‐1 hi Tim3 + subset and amplifying the PD‐1 int TCF + population. DFB dampens CCL2 and preserves progenitor terminal exhausted T cells in the obese microenvironment to restrain colorectal cancer progression.